English for Pharmacy Students: A Needs Analysis for Instructional Material Development - Nurpahmi, Sitti; Fadhilah Rahman, Indah (ETERNAL (English, Teaching, Learning and Research Journal), 2024)
The ability to use English effectively in professional and academic settings is essential for pharmacy students in today’s globalized health and pharmaceutical industries. However, many pharmacy programs still rely on general English courses that do not reflect the specific communicative tasks and discourse practices required in the pharmacy profession. This study aims to analyze the English language needs of pharmacy students as a basis for developing relevant instructional materials. Using a mixed-methods design, data were collected from 80 undergraduate pharmacy students, four lecturers, and two professional pharmacists through questionnaires, interviews, and document analysis. Quantitative data were analyzed using descriptive statistics, while qualitative data were interpreted through thematic analysis. The findings reveal that pharmacy students need greater competence in reading and writing scientific texts, mastering technical vocabulary, and developing speaking skills for patient counseling and professional collaboration. The results emphasize the importance of designing English for Specific Purposes (ESP) materials that are context-based, skill-integrated, and aligned with real-world pharmacy communication. The study contributes practical insights for ESP curriculum designers, material developers, and English instructors in health-related disciplines.